Processing of potato for domestic and commercial use - Bandana, Bandana; Sharma, Vineet; Singh, Brajesh; Kumar, Manoj (Indian Horticulture, 2020)
Potato is one of the traditional and most used food items in India. Potatoes are versatile for a variety of culinary uses in most Indian households and are used for many purposes throughout the year. Global consumption of potatoes is shifting from fresh potatoes to value-added and processed food products. Processing has the potential to enable potatoes to achieve industrial status. This will not only create more employment but will also improve nutrition and increase the income of potato farmers.